Dysuria: An unusual complication of pubic exostosis in a child 10 years - Merouane Nour; Mohamed El Fatri Lamghari; Mohamed Belahcen; Tarik Madhi (Elsevier, 2020)
Exostosis or osteochondromas are benign bone tumors frequently.These benign tumors may be symptomatic or be manifested on the occasion of a complication. We report the case of a child boy 1O years, admitted to our training multiple exostosis, with a location iliopubic left that proved by painful induration left of the base of the penis. Induration the increasing volume, it bothered the child during urination. Conventional radiography and CT were in favor of a pedunculated osteochondroma of the left iliac ramus compressing the urethra. The child underwent surgical tumor resection and pathological examination confirmed the diagnosis of osteochondroma. The evolution was good with disappearance of urinary symptoms down two years without recurrence. Keywords: Exostosis, Osteochondroma, Dysuria, Iliopubic, Child